Optimization The Role of Sharia Bank in National Economic Recovery Through Results-Based Micro-Finance - Yusmat, Muammar Arafat; Bakri, Adznan Noor; Rizaldy, Muhamad Rizky (IKONOMIKA, 2023)
The problem in this research is that the Covid 19 pandemic that occurred in early 2020 resulted in a decrease in the performance of small, micro and medium enterprises. The most felt impact is the difficulty in paying off debt in the banking sector so that not a few MSME business actors take the path of restructuring their loans. The purpose of this research is to design a formulation of a sharia-based micro business financing model formulation. This research aims to create an appropriate microfinance model so that Islamic banks can play an optimal role in the national economic recovery program. This study found the right model for financing if you want to use a maharajah contract: (1) paying profit-sharing salaries, (2) buying ideas, (3) profit sharing without salary, and (4) instrumental alternatives such as endowments. This study uses a research method with a qualitative approach. All data comes from in-depth interviews and FGDs with customers, Islamic banks as practitioners, and several Islamic banking experts as academics. All information is processed using a process hierarchy analysis technique or AHP to produce the right model for micro business financing